The specifics of integrating distance learning technologies with traditional classroom instruction: How to design educational curricula in modern education? - Natalia Zakharova; Svetlana Frumina; Liudmila Lobuteva; Suad Alwaely (Heliyon, 2024)
The active and widespread transition to distance learning modalities was prompted by the COVID-19 pandemic and is currently considered a prospective paradigm for the development of the education system. This shift necessitates the creation of corresponding curricula and programs capable of fostering student competencies through online and blended learning. The purpose of this research is to examine the specifics and formulate an algorithm for the development of educational programs incorporating distance and blended learning technologies. Analytical, sociological (utilizing semi-structured surveys administered to 96 educators and 128 students on the subject of distance and blended learning and its methodological support), modeling, and mathematical-statistical methods (Student's t-test and analysis of variance ANOVA) were employed in this study. The survey confirmed the hypothesis of differences in attitudes toward distance learning among students and educators. Educational needs and challenges were identified, leading to the development of an algorithm for designing educational programs integrating distance and blended learning technologies. An algorithm has been devised for the development of educational programs based on the integration of distance and blended learning technologies. The study underscores the importance of continuity across educational levels and the early cultivation of distance learning skills. Prospective research endeavors are intended to be directed toward the examination of the organization of distance and blended learning for students with special educational needs.